Optimalisasi Pengelolaan Kualitas Air Terhadap Kelangsungan Hidup Udang Vaname (Litopenaeus Vannamei) di Farm Vannamei Reborn Probolinggo Jawa Timur - Hamka Oktasari; Mariam Mariam; Andi Baso Adil Natsir (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2024)
Water quality management means efforts made to maintain water parameters so that they are in a safe condition, the standard of cultivation mediab required. Poor water quality will be the start of disease for shrimp and cn cause stress. Poor water quality can affect growth, metabolic processes and survival. Shrimp become low. The aim of this research is to find out whether the optimal quality management for the survival of vannamei shrimp (litopenaeus vannamei) at the reborn vannamei farm is optimal. The data alalysis method in this research uses quantitative descriptive analiysis techniques.The survival percentage of vaname shirmp from plot A 93,78%, plot B 92,68%, plot C 92,40% and plot D 90,38%. All plot showed a high survival rate from the standard value set by PT. Proteina Central Prima or CP Prima.